THz oscillations in DNA monomers, dimers and trimers - Lambropoulos, K.; Kaklamanis, K.; Georgiadis, G; Theodorakou, M.; Chatzieleftheriou, M.; Morphis, A.; Tassi, M.; Simserides, C. (Progress in Electromagnetics Research Symposium, 2015)
We call monomer a B-DNA base-pair and study electron or hole oscillations in monomers, dimers and trimers. We employ two Tight Binding (TB) approaches: (I) at the base-pair level, using the on-site energies of the base-pairs and the hopping parameters between successive base-pairs and (II) at the single-base level, using the on-site energies of the bases and the hopping parameters between neighboring bases. With (II), for monomers, we predict oscillations with frequency f ≈ 50-550 THz. With (I), for dimers, we predict oscillations with f ≈ 0.25-100THz, for trimers made of identical monomers f ≈ 0.5-33 THz. In other cases, the oscillations may be not strictly periodic, but Fourier analysis shows similar frequency content. For dimers, we compare approaches (I) and (II). Finally, we present calculations with (III) RealTime Time-Dependent Density Functional Theory (RT-TDDFT) for the adenine-thymine (A-T) and the guanine-cytosine (G-C) base-pairs. It seems that a non conventional source or receiver of electromagnetic radiation with f from fractions to THz to just below PHz could be envisaged.  ISSN: 15599450 ISBN: 978-193414230-1